The technical assessment of individual performance in rugby union players - Green, Andrew Craig (My University, 2016)
Performance in Rugby Union relies on a wide variety of contributions of different individual skills. Individual tasks, such as passing, kicking or scrummaging are dependent on an individual’s ability and may vary according to a player’s playing position. The focus of this thesis is a series of studies which have assessed the performance of individual rugby players (particularly related to the assessment of passing, kicking and scrummaging) and to evaluate such performance in relation to factors (most often kinematic factors) which have been identified and correlated to better performance. The main body of this thesis includes seven studies, in the form of original papers, which firstly describe the factors which contribute to rugby passing accuracy (two studies), thereafter two studies which focus on kicking success are described. The final three studies describe the development of a new device for measuring individual scrummaging performance. These studies also investigated: the role of body positioning in the generation of scrummaging force; and assessed how such factors may respond to the fatigue experienced over the duration of a rugby game. One skill that all rugby players require is the ability to effectively pass the ball to another player. Two original research studies are presented in this thesis that describe multiple approaches to accomplishing passes in rugby players. A target frame was constructed, and the ball position relative to the centre of the target frame was recorded and reported as the accuracy error distance. The first study of this thesis assessed the accuracy of the running pass using self-selected passing strategies. Two strategies were identified: in-step passing and out-of-step passing, although differences in the step sequence resulted in no change in the pass accuracy. The second study evaluated the differences in accuracy and kinematic strategies used to execute the ground pass. Passes performed using a side-on body orientation were more accurate than those performed using a front-on body orientation. The two body orientations utilised different kinematic strategies: front-on relied on torso and pelvic rotations, whereas the side-on relied less on trunk rotations and utilised greater extension angles of the stance arm. Match victory can also be determined by individual kicking success, but in this case is reliant on the role of individual kickers in a team. In the third study, kinematic predictors of place kicking accuracy and distance were explored. Larger axial torso and pelvic rotations were related to further place kicks, and greater extensions of the stance arm was related to more accurate place kicks. However larger torso rotations, which were positively related to kicking distance, were negatively related to kick accuracy. The fourth study was devised to compare the kinematic sequences of two points scoring kicking types. The comparisons suggest that the body kinematics used during the place and drop kicks were not different, although kicking distances were further in the place kick. The fifth study of this thesis evaluated the feasibility of a custom individual scrummaging ergometer. The design, calibration, and measurement accuracy of the individual scrum ergometer are presented. Application of the ergometer revealed differences in individual scrummaging attributes, such as position of force application and centre of pressure variation, of players in different playing positions. No differences were observed in the force magnitude between playing positions. The sixth study investigated individual kinematic scrum performance using conventional kinematic techniques and the custom individual scrum ergometer. The results highlight the role of a lower body height and wider stance in the attainment of greater individual scrummaging forces. No static kinematic variables were related to individual scrum performance. The final study investigated the effects of fatigue resulting from a simulated rugby match on individual scrummaging kinetics and kinematics. Although an increase in psychological and physiological markers of fatigue were observed, no scrummaging v differences were noted in peak forces or in body kinematics at peak force following the rugby match simulation. In conclusion, the identification of performance related factors and the invalidation of others which have been identified in this body of work, may provide an opportunity for performance tailoring strategies of individual players, selection strategies for teams or even the tailoring of training practices to optimise performance. As an initial set of studies, however, many of these factors still need reassessment and validation by subsequent research and therefore this work has provided a number of research possibilities for later studies. To this end, a suggested topic of ensuing research may be to assess the repeatability of predictive power of the variables identified here, whether they are uniformly predictive over time or in different subject groups and lastly whether the individual performances (which were the focus of these studies) are translatable into team performance.
A thesis submitted to the Faculty of Health Science, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree Doctor of Philosophy. Johannesburg, 2016
Keywords: Sports